Combined immunoglobulin G kappa nephropathy: monoclonal immunoglobulin deposition disease and proximal tubulopathy: monoclonal gammopathy of renal significance or smoldering multiple myeloma Case report and review of literature. Issue 1 (2017) - Zakharova, Elena V; Stolyarevich, Ekaterina S; Vorobyeva, Olga A; Nikitin, Eugeny A
No abstract available